Paleomagnetism of the Upper Cretaceous Daijiaping Formation red beds in the Chaling Basin, Hunan Province, China - Dengkui Jin; Yongxiang Li (地质科技通报, 2023)
Objective Red beds are widely used in palaeomagnetic studies as they can carry stable natural remanence. Most previous studies on red beds have mainly focused on lacustrine-fluvial facies, with limited targeting the aeolian red beds. Consequently, the influence of aeolian deposition processes and sedimentary environments on remanence records remains poorly understood. Methods In this study, we conducted a palaeomagnetic investigation of the red beds from the Upper Cretaceous Daijiaping Formation in the Chaling Basin, Hunan Province, China, to compare the stability and reliability of remanence in aeolian and lacustrine-fluvial red beds. Results Rock magnetic results indicate that magnetite, maghemite and hematite are the dominant magnetic remanence carriers. Specimens were subjected to stepwise thermal demagnetization, and only 1/6 of the specimens yielded characteristic remanent magnetisations (ChRMs). Although the mean directions of ChRM in both aeolian(Ds=222.7°, Is=-43.3°, κ=5.9, α95=20.6°, n=11) and lacustrine-fluvial (Ds=204.6°, Is=-47.8°, κ=2.4, α95=23.1°, n=28) samples are statistically indistinguishable, the distribution of individual ChRM directions is scattered, as evidenced by the large α95 values. Thin section observation reveals that the aeolian samples are predominantly composed of fine grains, with some coarser grains and almost no interstitial fillings compared with the lacustrine-fluvial red beds. This makes them susceptible to physical disturbance and subsequent chemical alteration, which compromises the stability of their remanence records. Analysis of palaeomagnetic data of specimens from different positions of an aeolian foreset bed reveals that the reliability of remanence is significantly influenced by aeolian depositional processes in case the angle between the foreset bed and the bedding plane is larger than 20°. Statistical analysis of palaeomagnetic data previously published from the Cretaceous red beds in South China and these in this study suggests that the remanence records in the Cretaceous aeolian red beds in South China tend to be less stable and less reliable, compared with that of the coeval lacustrine-fluvial red beds. It is probably because of their loose structure and low hematite content, which hinders the acquisition of primary remanence and makes them susceptible to diagenetic alteration. Conclusion These findings provide valuable insights for studying the stability and reliability of remanence in aeolian red beds and their application in palaeomagnetic study.